2013
DOI: 10.1038/ijo.2013.146
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction promotes physical inactivity and obesity in female mice

Abstract: Background Environmental exposures during critical periods of prenatal and early postnatal life affect the development of mammalian body weight regulatory mechanisms, influencing lifelong risk of obesity. The specific biologic processes that mediate the persistence of such effects, however, remain poorly understood. Objective The objectives were to determine the developmental timing and physiological basis of the obesity-promoting effect previously reported in offspring of obese agouti viable yellow (Avy/a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 47 publications
8
41
1
Order By: Relevance
“…Animal experiments imply that under-nutrition in fetal life, followed by postnatal weight gain, is associated with reduced motor activity (65,66) and increased sedentary behavior (67). Some human data tend to support these observations.…”
Section: Birth Weightmentioning
confidence: 65%
“…Animal experiments imply that under-nutrition in fetal life, followed by postnatal weight gain, is associated with reduced motor activity (65,66) and increased sedentary behavior (67). Some human data tend to support these observations.…”
Section: Birth Weightmentioning
confidence: 65%
“…Most interestingly, fetal growth restriction and subsequent catch-up growth led to increased body weight and adiposity in adulthood, but only in female offspring. Overall, although these data indicate that growth restriction during prenatal development is an essential component of the programming mechanism (22) , they do not rule out a potential critical role for catch-up growth during the suckling period.…”
mentioning
confidence: 97%
“…Whereas food intake of female OL offspring was not different from that of controls, their levels of physical activity (home cage activity) and energy expenditure were reduced directly after weaning, and remained so in adulthood. In fact, the persistently blunted spontaneous physical activity (SPA) of OL females appeared to completely explain their increased adiposity as adults (22) . Notably, recent studies in three different human populations showed that perinatal undernutrition leads to increased obesity in adulthood, specifically in females (23) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal growth restriction due to reduced food intake reduced physical activity and energy expenditure, and increased obesity in female, not male offspring mice [17]. Diet with decreased percent of protein fed to rat mothers during weaning decreased in the offspring slightly body weight and fatness along with increased economy of following growth (expressed as g diet /g body weight increase), increased spontaneous PA level in running wheels and reduced experimental cardiac necrosis and mortality after isoprenaline application in adult age [6,18,19].…”
Section: Interrelationships Between Early Nutrition Related To Physicmentioning
confidence: 99%